PENDAMPINGAN KELOMPOK PETERNAKAN SAPI POTONG DALAM PENGELOLAAN PEMBUKUAN DI DESA LIANG KECAMATAN SALAHUTU KABUPATEN MALUKU TENGAH - Matatula, Michel Johan; Sarfan, Riri (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2025)
Economically, beef cattle farming is very supportive of economic growth in rural communities because most of them are raised and developed as smallholder livestock businesses. The cattle farming business in Liang Village has the potential to be developed because it is a source of income for the community. The problem faced by beef cattle farmers in Liang Village is that they do not yet have skills in financial recording, which affects decision-making, especially in assessing the feasibility of the business being run. The purpose of implementing this PkM is to provide an understanding of the importance of recording financial transactions in beef cattle farming so that farmers are able to make simple bookkeeping so that they can assess the feasibility of the business being run. The stages of activity begin with observation and approaches to obtain information about business conditions and the needs of beef cattle farmers. The next stage is counseling, discussion and direct practice on how to record production costs and income into simple bookkeeping, so that farmers can assess the feasibility of the business being run. The results is Service Program show that the level of knowledge of livestock farmers regarding livestock financial management is only 40%, but increased to 85% after the Service Program activity. Participants' skills and understanding in financial management increased from 35% before the activity to 80% after. This shows that the Service Program activities provided have a positive impact in increasing the understanding and skills of farmers in managing their livestock business finances.